Mechanisms of a coniferous woodland persistence under drought and heat. (16th April 2019) - McDowell, Nate G; Grossiord, Charlotte; Adams, Henry D; Pinzón-Navarro, Sara; Mackay, D Scott; Breshears, David D; Allen, Craig D; Borrego, Isaac; Dickman, L Turin; Collins, Adam; Gaylord, Monica; McBranch, Natalie; et al.
Abstract: Predictions of warmer droughts causing increasing forest mortality are becoming abundant, yet few studies have investigated the mechanisms of forest persistence. To examine the resistance of forests to warmer droughts, we used a five-year precipitation reduction (∼45% removal), heat (+4 °C above ambient) and combined drought and heat experiment in an isolated stand of mature Pinus edulis-Juniperus monosperma . Despite severe experimental drought and heating, no trees died, and we observed only minor evidence of hydraulic failure or carbon starvation. Two mechanisms promoting survival were supported. First, access to bedrock water, or 'hydraulic refugia' aided trees in their resistance to the experimental conditions. Second, the isolation of this stand amongst a landscape of dead trees precluded ingress by Ips confusus, frequently the ultimate biotic mortality agent of piñon. These combined abiotic and biotic landscape-scale processes can moderate the impacts of future droughts on tree mortality by enabling tree avoidance of hydraulic failure, carbon starvation, and exposure to attacking abiotic agents.